SEL BETA PANKREAS SINTESIS DAN SEKRESI INSULIN - Banjarnahor, Eka; Wangko, Sunny (Jurnal Biomedik : JBM, 2012)
Abstract: Insulin synthesis and secretion are done by pancreatic beta cells. Preceding the insulin synthesis, there is a gen translation in chromosome 11 that produces insulin, packed in secretory granules. Insulin secretion is induced by the alteration of blood glucose levels, resulting in the occurence of intracellular reactions preceded by changes of ATP/ADP ratios that trigger the depolarisation of plasma membranes. Furthermore, extracellular Ca2+ ions move inward to beta cells to activate exocytosis. There are still many unknown problems so far in either the synthesis or secretion of insulin that cause unfulfilled insulin needs in the body.Keywords: beta cells, insulin, synthesis, secretionAbstrak: Sintesis dan sekresi insulin dilakukan oleh sel beta pankreas. Sintesis insulin diawali oleh salinan gen pada kromosom 11, yang akan menghasilkan insulin, di kemas di dalam granul-granul sekretorik. Sekresi insulin diinduksi oleh perubahan kadar glukosa, yang berakibat terjadinya reaksi intrasel yang diikuti adanya perbedaan rasio ATP/ADP yang memicu reaksi depolarisasi membran plasma. Sebagai akibat lanjut Ca2+ ekstrasel akan masuk ke dalam sel beta yang berfungsi mengaktifkan eksositosis. Sampai saat ini masih banyak ditemui masalah baik dalam hal sintesis maupun sekresi insulin yang mengakibatkan kebutuhan insulin tubuh tidak terpenuhi.Kata kunci: sel beta, insulin, sintesis, sekresi